Rozwiązane

Proszę pomóżcie

y = (x + 10) (x - 20) =
y = 6 (x - 1/2) (x - 1/3) =
y = 2(x+3) (3x - 4 )=
y= (2r -4) (2r - 1) =
y = ( 2 x + 1) (3x + 1) =
y = (5x - 2) ( 4x - 3) =
y = - x (x + 3) =
y = 1/2x (2x - 1)
y = 97 -3x) x



Odpowiedź :

Odpowiedź:

y=x2-20x-200+10x=x2-10x-200

y=6(x2-1/3x-1/2x-1/6)=6x2-2x-3x-1=6x2-5x-1

y=2(3x2-4x+9x-12)=6x2-8x+18x-24=6x2+10x-24

y=4r2-2r-8r-4=4r2-10r-4

y=6x2+2x+3x+1=6x2+5x+1

y=20x2-15x-8x-6=20x2-23x-6

y=-x2-3x

y=x2-1/2x

y=-3x2+97

Szczegółowe wyjaśnienie:

Myslę ze pomogłam. Proszę naj